Implementation of Cooperative Learning Model: Student Teams Achievement Division (STAD) In Fiqh Learning - Maryam Hasim Hasibuan; Anni Marhamah; Ali Jusri Pohan (Prodi Pendidikan Keagamaan Islam, 2025)
This study aimed to describe the implementation of the Cooperative Learning model of the Student Teams Achievement Division (STAD) type in Fiqh learning at MTs Negeri 2 Mandailing Natal. The research focuses on preparation, implementation, advantages, and disadvantages of applying the STAD model. This research uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The results show that teachers prepared lesson plans and teaching media appropriately. The learning process includes material presentation, heterogeneous group division, discussion activities, individual quizzes, assessment, and group rewards. The STAD model successfully increased students’ activeness, cooperation, and responsibility during Fiqh learning, although it required more time and teacher readiness.